Lost Circulation Effect of Bagasse, Coconut Fibers, Banana Tree Bark and Sawdust on Cement Grade G Characteristics - Samuel Renjaan; Sugiatmo Kasmungin; Abdul Hamid (Journal of Earth Energy Science, Engineering, and Technology, 2018)
The quality of cement is very important because it will greatly help the production well activities especially to make the construction of wells can last long. In this study the influence of lost circulation material (LCM) was analyzed, such as Bagasse, Coconut Fibers, Banana Tree Bark and Sawdust on the physical properties of G-class cement such as rheology, density, free water content, thickening time, and compressive strength. This research was conducted in the laboratory by varying the percentage of LCM from 0% to 6% and temperature from 95oF to 200oF. From this research, it can be known that the addition of LCM can change the physical properties of cement. The highest increase of plastic viscosity (PV) and yield point (YP) values was occurred at 6% concentration of Bagasse, Coconut Fibers, Banana Tree Bark and Sawdust that was 105 cp – 92 lbs/100ft2, 105 cp – 90 lbs/100ft2, 90 cp – 110 lbs/100ft2, and 95 cp – 110 lbs/ft2. The longest thickening time was occurred at 6% concentration of Bagasse, Coconut Fibers, Banana Tree Bark and Sawdust with a soaking temperature of 200 oF which that was 65 minutes, 60 minutes, 66 minutes, and 63 minutes. The highest reduction of density value occured at 6% concentration of Bagasse, Coconut Fibers, Banana Tree Bark and Sawdust that was 15.0 ppg, 15.2 ppg, 15.2 ppg and 15.0 ppg. The decrease in the highest free water content value occurs with the addition of 6% in each type of LCM, namely 0.9 ml, 0.95 ml, 0.9 ml and 1 ml. The increase in the strong press rate occurs in the addition of 1% sugar cane, which is 2838 psi; 1% Coconut fibre is 2926 psi, 0.5% of the banana tree bark is 3080 psi and 1% of sawdust is 2728 psi all at 200 º temperature.